Dessalinização de água em uma planta de energia solar concentrada: modelagem e análise termodinâmica - Medeiros, Vítor Silva (2021)
Several countries are already facing water shortages as a result of increased consumption and climate change over the years. Countries, mainly in the Persian Gulf region, turned to desalination, an energy-intensive process that extracts salt from water. Fortunately, most arid regions that suffer from water scarcity are located in places with high solar irradiance, in other words, they have solar energy potential. Integrating Concentrated Solar Power (CSP) and desalination technologies is a way to simultaneously produce desalinated water and energy. Thus, the objective of this work was to develop a model for thermodynamic analysis, and verification of the feasibility of desalinated water and energy cogeneration systems. A model describing the Multi-Effect Distillation (MED) process together with a Thermal Vapor Compressor (TVC) system was implemented and validated against data from commercial plants available in the literature. The MED desalination model worked in conjunction with a computer program to simulate the performance of CSP parabolic trough systems. In addition, the compatibility between Reverse Osmosis (RO) process and CSP technology was also analyzed. The city of Fortaleza-CE was used as a case study for the feasibility analysis of installing concentrated solar power and desalination technologies. The results of the studies showed that the MED, MED-TVC and RO desalination systems combined with the CSP technology present good performances under the simulated weather conditions, and the CSP+RO option presents a production advantage over the other configurations.